Chinese science in relaxation: Piano playing technique redefined - Loo, Fung Ying; Loo, Fung Chiat (American-Eurasian Network for Scientific Information, Jordan, 2011)
This study first explores the issue of muscular contraction and relaxation in piano playing from a Chinese science perspective. The main aim of this article is to examine the classic Chinese concept of yin and yang and how it forms the movement principle in taijiquan, then goes on to investigate this further as applied to the concept of relaxation in piano playing. Relaxation itself can be contentious especially when it is employed as a technique of movement which contradict its original character of passivity. In this paper, views about relaxation from piano pedagogues will be discussed. The research took on a practice-led approach. This article highlights motion analysis in a philosophical perspective. The character of relaxation is redefined using the concept of yin and yang as an analytical tool.